Arterial access site and outcomes in patients undergoing percutaneous coronary intervention with and without vorapaxar. Issue 2 (23rd December 2015) - Déry, Jean‐Pierre; Mahaffey, Kenneth W.; Tricoci, Pierluigi; White, Harvey D.; Podder, Mohua; Westerhout, Cynthia M.; Moliterno, David J.; Harrington, Robert A.; Chen, Edmond; Strony, John; Van de Werf, Frans; Ziada, Khaled M.; et al.
Abstract : Objectives: We evaluated outcomes associated with transradial vs. transfemoral approaches and vorapaxar in acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) in the TRACER trial. Background: Vorapaxar reduces ischemic events but increases the risk of major bleeding. Methods: We compared 30‐day and 2‐year major adverse cardiac events (MACE: cardiovascular death, myocardial infarction, stroke, recurrent ischemia with rehospitalization, and urgent coronary revascularization) and noncoronary artery bypass graft (CABG)‐related bleedings in 2, 192 transradial and 4, 880 transfemoral patients undergoing PCI after adjusting for confounding variables, including propensity for transradial access. Results: Overall, 30‐day GUSTO moderate/severe and non‐CABG TIMI major/minor bleeding occurred less frequently in transradial (0.9% vs. 2.0%, P  = 0.001) vs. transfemoral (1.1% vs. 2.5%, P  = 0.005) patients. A similar reduction was seen at 2 years (3.3% vs. 4.7%, P  = 0.008; 3.3% vs. 4.9%, P  < 0.001, respectively). Transradial was associated with an increased risk of ischemic events at 30 days (OR 1.38, 95% CI 1.11–1.72; P  = 0.004), driven primarily by increased periprocedural myocardial infarctions. At 2 years, rates of MACE were comparable (HR 1.14, 95% CI 0.98–1.33; P  = 0.096). Although bleeding rates were higher with vorapaxar in transfemoral vs. transradial patients, there was no significant treatment interaction. Also, the access site did not modulate the association between vorapaxar and MACE. Conclusions: Transradial access was associated with lower bleeding rates and similar long‐term ischemic outcomes, suggesting transradial access is safer than transfemoral access among ACS patients receiving potent antiplatelet therapies. Because of the nonrandomized allocation of arterial access, these results should be considered exploratory. © 2015 Wiley Periodicals, Inc.